Trade policy at the crossroads - the Indonesian story - Vanzetti, David (UN New YorkUS, 2005)
Provides an overview of the evolution of Indonesia's trade regime since the 1960s. Examines the structure of the Indonesian economy in relation to existing trade flows and protection levels. Uses a general equilibrium model to assess the effects of Indonesia pursuing alternative trade policy paths. Discusses the results from these sumulations. Focuses on timing and sequencing issues for Indonesia in progressing with further liberalization. Looks at implications for policies that may also be of value to other countries facing similar trade policy dilemmas.